PEMBERDAYAAN APARATUR DESA MELALUI PELATIHAN SISTEM INFORMASI DESA GUNA PENINGKATAN KUALITAS PELAYANAN ADMINISTRASI MASYARAKAT DI DESA TEGALWERU,KECAMATAN DAU,KABUPATEN MALANG - Alifiulahtin Utaminingsih; Irma Fitriana Ulfah; Andi Setiawan; Ratnaningsih Damayanti; Devi Farah Azizah (Jurnal Pengabdian Kepada Masyarakat (J-ABDIMAS), 2019)
Not yet optimal quality of administrative services to the community due to the limited ability to use Information Technology apparatus, therefore it is necessary to develop and assist the apparatus in developing IT-based village E-Gov optimally, so that village administration can run better. After knowing the capabilities of the village apparatus in IT utilization, then training, facilitation and mentoring of E-Gov were carried out for village officials to have the skills and abilities to improve the quality of administrative services for the people of Tegalweru Village, Dau District, Malang Regency.Enhancing IT capacity in implementing good governance related to efforts to develop insights and knowledge about E-Gov (mentoring E-Gov and E-Biling, etc.) to village officials (Village Heads, Village Secretaries and all other village apparatus) as an effort to improve the skills of IT use in an effort to improve the quality of services and reporting all village government activities quickly, precisely and effectively.